2021
DOI: 10.1186/s12884-021-04102-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factors associated with stillbirth in Zimbabwe – a cross sectional study

Abstract: Introduction 98% of the 2.6 million stillbirths per annum occur in low and middle income countries. However, understanding of risk factors for stillbirth in these settings is incomplete, hampering efforts to develop effective strategies to prevent deaths. Methods A cross-sectional study of eligible women on the postnatal ward at Mpilo Hospital, Zimbabwe was undertaken between 01/08/2018 and 31/03/2019 (n = 1779). Data were collected from birth reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…A recent study on stillbirths determinants reported similar findings of higher risk of stillbirth among those with prior experience of stillbirth (36). This is also in line with another similar study by Dube and Lavender (37) in Zimbabwe that reported similar findings. History of abortion in this study demonstrated statistical significance as predictor of perinatal mortality.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study on stillbirths determinants reported similar findings of higher risk of stillbirth among those with prior experience of stillbirth (36). This is also in line with another similar study by Dube and Lavender (37) in Zimbabwe that reported similar findings. History of abortion in this study demonstrated statistical significance as predictor of perinatal mortality.…”
Section: Discussionsupporting
confidence: 93%
“…The geographical distribution of the forty-one (41) included articles revealed that Eastern African countries accounted for the majority of the research (58.5%). Five (5) of the studies were carried out in Cameroon ( 1), (10-13), nineteen (19) of the investigations were carried out in Ethiopia ( 2), ( 3), (5-9), (14-25), 6 in Ghana ( 4), (26-30), 4 in Tanzania (31)(32)(33)(34), 4 in Nigeria (35)(36)(37)(38), 1 in Zimbabwe (39), 1 in Uganda ( 40), and 1 in Burkina Faso (41). Of those studies, 37 were carried out in institutions or using facility-based records, while 4 were carried out in the community using survey data from the general population.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In relation to the response rate, the primary articles incorporated in the meta-analysis ranged from 92.7-100%, and essentially all the studies had a good response rate. Forty (40) of the forty-one (41) studies were published (1)-( 30), (32)(33)(34)(35)(36)(37)(38)(39)(40)(41), while one (1) was unpublished (a PhD thesis) in reputable journals (31). Lastly, the primary studies included in the present systematic review and meta-analysis had a quality score of 8-10 out of 10 points.…”
Section: Study Characteristicsmentioning
confidence: 99%